Cetacean Research and Citizen Science in Kenya - Mwango’mbe, Michael Gilbert; Spilsbury, Jane; Trott, Steve; Nyunja, Judith; Wambiji, Nina; Collins, Tim; Gomes, Inês; Pérez-Jorge, Sergi (Frontiers in Marine Science, 2021)
In 2011, several non-governmental and government agencies established the Kenya Marine Mammal Network (KMMN) to provide a platform for the consistent collection of data on marine mammals along the Kenyan coast, identify areas of importance and engage marine users and the general public in marine mammal conservation. Prior to the KMMN, relatively little was known about marine mammals in Kenya, limiting conservation strategies. The KMMN collects data nationwide through dedicated surveys, opportunistic sightings and participative citizen science, currently involving more than 100 contributors. This paper reviews data on sightings and strandings for small cetaceans in Kenya collated by the KMMN. From 2011 to 2019, 792 records of 11 species of small cetaceans were documented. The most frequently reported inshore species were the Indo-Pacific bottlenose dolphin and Indian Ocean humpback dolphin. Offshore species, included killer whales, short-finned pilot whale and long-snouted spinner dolphin. Indo-Pacific bottlenose dolphins, long-snouted spinner dolphins, striped dolphins and Risso’s dolphins were recorded through stranding reports. The efforts of the KMMN were disseminated through international meetings (International Whaling Commission, World Marine Mammal Conference), national status reports, outreach and social media. Data has also supported the identification of three IUCN Important Marine Mammal Areas and one Area of Interest in Kenya. Further research is needed to improve estimates of cetacean abundance and distribution, particularly in unstudied coastal areas, and to assess the extent of anthropogenic threats associated with fisheries, coastal and port development, seismic exercises and unregulated tourism. The expansion of the network should benefit from the participation of remote coastal fishing communities, government research agencies, tourism and seismic operations, among others. The KMMN demonstrated the value of dedicated and citizen science data to enhance marine mammal conservation strategies to boost awareness and eco-tourism and to bring the public and science closer together, promoting research and effective conservation efforts.